Optimising and managing an integrated supply chain strategy for a modern petrochemical manufacturing enterprise - Botha, Christiaan Johannes (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1999.